(untitled) (Revista Educação, Artes e Inclusão, 2023)
This article aimed to analyze the perception of Specialized Educational Service (AEE) teachers about the physical and material conditions of Multifunctional Resource Rooms (SRM) in the Piemonte region of Diamantina, Bahia. For the data collection of this research, a questionnaire containing closed questions and multiple alternatives was produced. In addition to favoring the capture of respondents’ opinions in previously defined response options, the questionnaire allows reaching a large population, a lower level of training of respondents and guarantees the anonymity of the identities of the participating subjects. Summarizing the majority perception of the teachers, it was possible to observe that the items considered good were: size of the physical space, quantity of materials for the AEE, permanent and consumption materials, lighting, internal noise, cleanliness of the environment and safety around the school where SRM is deployed. Accessibility and adaptations were curiously divided into good and regular. The offer of Assistive Technologies was considered regular. However the level of outside noise is regular, ventilation and temperature were considered poor.